2011
DOI: 10.7863/jum.2011.30.5.677
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Sonographic Results for Graf Type 2a Hips

Abstract: Type 2a hips may worsen sonographically at a rate of 5.6%; hence, sonographic follow-up is needed. Instability, central nervous system anomalies, and unilateral type 2a hips were found to be independent predictors of sonographic worsening. Our study shows that cases with these risk factors should be followed more carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
4
8
0
1
Order By: Relevance
“…The quality of treatment and treatment outcomes were comparable to those reported for children in resource-rich countries [10]. A recent study in Turkey observed worsening of Type 2a hips and therefore recommends a close follow-up for patients with an initial Type 2a diagnosis [11]. This recommendation is supported by the findings from our study: We found that 25 initially controlled Type 2a hips evolved into Type 2c-3 hips at first follow-up.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The quality of treatment and treatment outcomes were comparable to those reported for children in resource-rich countries [10]. A recent study in Turkey observed worsening of Type 2a hips and therefore recommends a close follow-up for patients with an initial Type 2a diagnosis [11]. This recommendation is supported by the findings from our study: We found that 25 initially controlled Type 2a hips evolved into Type 2c-3 hips at first follow-up.…”
Section: Discussionsupporting
confidence: 85%
“…This recommendation is supported by the findings from our study: We found that 25 initially controlled Type 2a hips evolved into Type 2c-3 hips at first follow-up. As in the study reported from Turkey [11] all of these hips recovered with adequate treatment until second follow-up. In our birth cohort all patients with a 2c to 4 type hip have been treated and therefore we cannot assess whether or not these hips would have resolved spontaneously.…”
Section: Discussionsupporting
confidence: 62%
“…Hips with a slightly shallow acetabulum and rounded bony rim before 3 months of age are considered developmentally immature and are classified as Graf type IIa (Figure 1) [22]. The α angle is 50˚ -59˚, whereas the β angle is 55˚ -77˚.…”
Section: Graf Iiamentioning
confidence: 99%
“…These hips are clinically reduced and stable [23]. Open Journal of Pediatrics [22]. About 85% of type IIa(−) hips reach normality without any treatment at the end of 3 months [24].…”
Section: Graf Iiamentioning
confidence: 99%
“…İlk US incelemede tip 2a lehine değerlendirilen kalçaların 3 ay içerisinde %84-97'si kendiliğinden düzeldiği, %3-5 oranda ise displaziye doğru ilerleme gösterdiği bildirilmiştir. Üçüncü ayında tip 1a kalçaya dönüşmeyen yenidoğanlarda ortopedik tedavi gerekliliği doğduğu belirtilmiştir 6,11,12 .…”
Section: İstatiksel Yöntemunclassified